Rain Loads : 2024 IBC and ASCE/SEI 7-22 - Fanella, David A. (McGraw-Hill's AccessEngineering., 2023)
This Excel workbook determines rain loads in accordance with the 2024 IBC and ASCE/SEI 7-22. Rain load calculations are performed in imperial and metric units for roofs with drains, channel scuppers, closed scuppers, and circular scuppers.